Metodología del ingreso de datos de las redes eléctricas existentes y proyectadas al sistema GIS de la Empresa Eléctrica Regional del Sur. - Rodríguez Cueva, Eduardo Stalin (2014)
In the present research called “METODOLOGÍA DEL INGRESO DE DATOS DE LA REDES ELÉCTRICAS EXISTENTES Y PROYECTADAS AL SISTEMA GIS DE LA EMPRESA ELÉCTRICA REGIONAL DEL SUR” have such as general objective believe a geodatabase low model of date MultiSpeak for the company electric the south S.A. We use the descriptive-deductive methods. The technique use was: A program of software called multispeak where to analyze the benefits of an information system geographic SIG, analyzing our topology, digital drawings (substation-client), defining the class and believing cartographic basic. In the checking of some objectives an to obtain. The following results and conclusions. Obtain the interoperability of some systems, process or functions central electric, substation, circuit of medium and low tension, transformers and the ubication of customers inside of the operation and planification of the distribution, the energy conclude with a better quality of service and maintenance, plans the expansion, plans for the location of faults, the information technical of the components of georeferenced, helping adequate internal communication internal the company.